On Mannheim Partner Curves in E-3 - Orbay, Keziban; Kasap, Emin (Academic Journals, 2009)
The aim of this paper is to study the Mannheim partner curves in Euclidean space E-3. We obtain the relationships between the curvatures and the torsions of the Mannheim partner curves with respect to each other.
Keywords: Mannheim Partner Curves; Curvature; Torsion